Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2\left(y-1\right)-4\left(y-1\right)\\ =\left(y-1\right)\left(x^2-4\right)=\left(y-1\right)\left(x-2\right)\left(x+2\right)\)
1, = [(x-1)^2-y^2] : (x-y-1)
= (x+y-1).(x-y-1) : (x-y-1) = x+y-1
2, x^2-x-y^2+y = (x^2-y^2)-(x-y) = (x-y).(x+y) - (x-y) = (x-y).(x+y+1)
k mk nha
Khai triển hằng đẳng thức :
\(x^2+2xy+y^2=\left(x+y\right)^2\)
\(\left(x+y\right)^2=\left(x+y\right)\left(x+y\right)\)
TL:
\(\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=x^3+x^2y+xy^2-yx^2-xy^2-y^3\)
\(=x^3-y^3\)
\(\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=x\left(x^2+xy+y^2\right)-y\left(x^2+xy+y^2\right)\)
\(=\left(x^3+x^2y+xy^2\right)-\left(x^2y+xy^2+y^3\right)\)
\(=x^3+x^2y+xy^2-x^2y-xy^2-y^3\)
\(=x^3-y^3\)
\(y^2+y+y+1\)
\(=y^2+2y+1\)
\(=\left(y+1\right)^2\)
Trả lời:
y2 + y + y + 1
= y2 + 2y + 1
= ( y + 1 )2